Improved HRTEM image processing methods and the application on soot nanostructure analysis for GDI engine. (1st May 2020) - Zhang, Zhou; Zhang, Wenbin; Awad, Omar I.; Ma, Xiao; Pan, Suozhu; Xu, Hongming; Shuai, Shijin
Highlights: The interlayer spacing can be automatically calculated by finding LCS. The GFBM is improved by using extended range and adaptive filters. The results from two kinds of image processing methods are compared. The nanostructures of the GDI engine soot are analyzed in detail. Abstract: A novel algorithm based on finding Longest common subsequence is coupled to the conventional method to automatically calculate the interlayer spacing of soot. The Gabor filter-based method (GFBM) is also improved by revising the parameter setting and response surface calculation. Firstly, the results of the two methods are compared and correlated. It is found that the interlayer spacings from the two methods are highly positively correlated. The fringe interlayer spacing decreases with the modulation strength increasing; the modulation strength can be regarded as an indicator of the degree of carbonization. The nanostructures of soot particles that are emitted from the gasoline direct injection (GDI) engine analyzed. The results reveal that the GDI engine soot particles possess a core-shell nanostructure. However, the shell is not entirely connected, and the stacks are surrounded by amorphous structures. The distribution of the interlayer spacing does not follow a normal distribution or log-normal distribution. The soot particles from the idle condition have a maximum interlayer spacing. The smallest interlayer spacing and a mid-level modulation strength were at 2000 r/min-3 bar, while at 2000 r/min-5 bar case, the highest modulation strength, and the second smallest interlayer spacing have been detected. The results of this study indicate that the interlayer spacing of soot particles increases with engine load and decreases with the increase of engine speed.